Kepercayaan Gen X terhadap Informasi di Media Sosial - Nova Nadifah; Atie Rachmiatie (UNISBA Press, 2022)
Abstract. The phenomenon of Indonesian people's media consumption patterns, especially generation X, who are mostly still technologically illiterate, raises questions to analyze the Gen X Audience Reception in the Kasomalang Market Traders Association Community on the Consumption of Information